AUGMENTED REALITY HYDRANT PEMADAM KEBAKARAN BERBASIS ANDROID - Sintya Dewi, Putri; Sudarma, Made; Care Khrisne, Duman (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i04.p6, 2020)
Augmented Reality (AR) is a technology used to display a 3-dimensional animated object with marker as a medium for displaying 3-dimensional animation in real time. Augmented Reality Hydrant for Fire Extinguishers Based on Android is an application used for learning media in the introduction of fire extinguishers with the aim of making it easier for the public or firefighters to find out their form and function through this application. The Fire Extinguisher Hydrant Augmented Reality application is made in several stages, namely identifying problems, determining goals and objectives, analyzing needs, designing systems, designing designs, making systems and testing systems. This Android-based Augmented Reality Hydrant can display several Hydrant objects or Fire Extinguishers and display information about these objects.